Stability Constant of Transition Metal Ions Complex with1-Carboxamido-3,5-diaryl-4-aroylpyrazoles - JAMODE, V.S.; KALE, A.S. (Asian Journal of Chemistry, 2010)
The interaction of transition metal ions Co(II), Cu(II) and Ni(II) with 1-carboxamido-3-(2-hydroxy-5-chlorophenyl)-4-benzoyl-5-phenylpyrazole (L1) and 1-carboxamido-3-(2-hydroxy-5-chlorophenyl)-4-benzoyl-5-(4-methoxy phenyl)-pyrazole (L2) have been investigated by pH-metric technique at 0.1 M ionic strength and at 27 ± 0.1 °C in 70% DMF-water medium. Co(Il), Cu(II) and Ni(II) ions form 1 : 1 and 1 : 2 complexes with ligands L1 and L2, respectively. Ligand L1 is found a better chelating agent than L2 because of higher values of log K1 and K2.